Screening of a Library of Recombinant Schistosoma mansoni Proteins With Sera From Murine and Human Controlled Infections Identifies Early Serological Markers. (10th June 2020) - Crosnier, Cécile; Hokke, Cornelis H; Protasio, Anna V; Brandt, Cordelia; Rinaldi, Gabriel; Langenberg, Marijke C C; Clare, Simon; Janse, Jacqueline J; Wilson, Shona; Berriman, Matthew; Roestenberg, Meta; Wright, Gavin J
Abstract: Background: Schistosomiasis is a major global health problem caused by blood-dwelling parasitic worms, which is currently tackled primarily by mass administration of the drug praziquantel. Appropriate drug treatment strategies are informed by diagnostics that establish the prevalence and intensity of infection, which, in regions of low transmission, should be highly sensitive. Methods: To identify sensitive new serological markers of Schistosoma mansoni infections, we have compiled a recombinant protein library of parasite cell-surface and secreted proteins expressed in mammalian cells. Results: Together with a time series of sera samples from volunteers experimentally infected with a defined number of male parasites, we probed this protein library to identify several markers that can detect primary infections with as low as 10 parasites and as early as 5 weeks postinfection. Conclusions: These new markers could be further explored as valuable tools to detect ongoing and previous S mansoni infections, including in endemic regions where transmission is low. Abstract : A library of recombinant S mansoni cell-surface and secreted proteins was produced in mammalian cells for functional and epidemiological studies. Using human and mouse sera from experimentally controlled infections, we identified molecular markers of infection as early as 5 weeks.